2022
DOI: 10.1155/2022/5251930
|View full text |Cite
|
Sign up to set email alerts
|

Antitrypanosomal and Anthelminthic Properties of Ethanol Extracts of Carica papaya Linn. and Ceiba pentandra (L) Gaertn.

Abstract: The most common diseases that affect low-income countries are helminthosis and trypanosomosis. In Ghana, and in many other African countries, herbal treatment of various diseases is still common. In the present study, we sought to determine the antitrypanosomal and anthelminthic activities of Carica papaya and Ceiba pentandra. The ethanol extracts of Carica papaya stem bark (PPSe) and leaves (PPLe) and ethanol extracts of Ceiba pentandra stem bark (CPSe) and leaves (CPLe) were screened against Trypanosoma bruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Antihemintic activity was also observed, killing Phetima posthuma after the experimental exposure time at 2.5, 5 and 10 mg/mL. These activities may be due to a high concentration and number of tannins and presence of n-hexadecanoic acid, a compound known for its antitrypanosomal potential (Wahab Obeng et al, 2022).…”
Section: Part Of Plantmentioning
confidence: 79%
“…Antihemintic activity was also observed, killing Phetima posthuma after the experimental exposure time at 2.5, 5 and 10 mg/mL. These activities may be due to a high concentration and number of tannins and presence of n-hexadecanoic acid, a compound known for its antitrypanosomal potential (Wahab Obeng et al, 2022).…”
Section: Part Of Plantmentioning
confidence: 79%
“…GC-MS analysis was used since it can detect and identify very small quantities of analytes in complex mixtures with high accuracy and specificity. The most predominant compound detected in the ethanol extract was 9-octadecenamide 9 Journal of Parasitology Research (Z)-which is an alkaloid and is known to have anthelmintic and antitrypanosomal properties [18]. The ethyl acetate extract had n-hexadecanoic acid and oleic acid as the most predominant compounds (Table 10).…”
Section: Discussionmentioning
confidence: 99%
“…The approach utilized by Wahab Obeng et al [ 18 ] was used to assess the anthelmintic modifying properties of extracts derived from M. zechiana . Upon testing various concentrations of these extracts, it was found that concentrations of 1.25 mg/mL did not induce paralysis or death in the worms, and this concentration was therefore designated as the subinhibitory concentration for the plant extracts.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to albendazole, the ethanol extract of C. papaya stem bark at 10mg/mL significantly caused worm paralysis at 0.62 minutes and death at 0.42 minutes after therapy (p<0.00001). In addition, the ethanol extract of C. papaya stem bark could increase the anthelmintic activity of albendazole through combination therapy of C. papaya stem bark extract 0.5mg/mL and albendazole 2.5mg/mL, which significantly accelerated the paralysis and death of worms to 0.62-and 0.99-minutes post-treatment (p<0.00001), respectively (13).…”
Section: Anthelmintic Activity Of Papaya Stem Bark Extractmentioning
confidence: 95%